The law of the iterated logarithm for random dynamical system with jumps and state-dependent jump intensity - Kubieniec, Joanna (Annales Mathematicae Silesianae, 2021)
In this paper our considerations are focused on some Markov chain associated with certain piecewise-deterministic Markov process with a statedependent jump intensity for which the exponential ergodicity was obtained in [4]. Using the results from [3] we show that the law of iterated logarithm holds for such a model.